Prevention and control of nosocomial infection in a certain endoscopy center under the management of COVID-19 with measures against Class B infectious diseases (新型冠状病毒感染“乙类乙管”下内窥镜中心感染防控与实践) - ZHANG Yuting (张玉婷); YANG Zhenbin (杨振斌); QIU Wei (邱伟); XIA Wenjuan (夏文娟) (中西医结合护理)
To summarized the prevention and control of nosocomial infection in a certain endoscopy center under the management of COVID-19 with measures against Class B infectious diseases. According to the hospital infection prevention and control requirements and related documents, combined with the actual situation of the clinical diagnosis and treatment in the endoscopy center, the infection control measures were formulated and implemented from the aspects of the management of the endoscopy center and the management and protection of the endoscopy staff and patients. From January 20, 2023 to March 20, 2023, 98 cases of digestive endoscopy were completed in the endoscopy center. No nosocomial infection occurred. Under the management of COVID-19 with measures against Class B infectious diseases, efforts should be made to enhance the emergency management and implementation of preoperative screening, therapeutic indications and diagnosis condition for digestive endoscopy. Strengthened protection of medical staff, cleaning and disinfection specification and establishment of the three-zone two-channel isolation wards are necessary to reduce the incidence of nosocomial infection in the endoscopy center. (总结新型冠状病毒感染“乙类乙管”下医院内窥镜中心感染防控与实践体会。根据医院感控要求及相关文件内容, 结合医院内窥镜中心临床诊疗的实际情况, 分别从内镜中心的管理及内镜工作人员和患者的管理与防护等方面制定和落实感控措施, 并进行效果评价。2023年1月20日—2023年3月20日, 内窥镜中心共完成消化内镜诊疗98例, 无院内感染发生。新型冠状病毒感染“乙类乙管”下, 消化内镜中心必须做好应急管理工作, 采取合理有效的措施, 切实做好术前患者各项筛查与管理工作, 严格把握消化内镜操作的适应证与诊疗条件, 做好内镜工作人员管理与防护工作, 严格遵守内镜室的洗消规范, 构建内镜室“三区两通道”隔离布局, 降低院内感染风险。)